Intraabdominal vein varix of fetal umbilical vein - Torres-Cepeda, Duly (2021)
Intra-abdominal vein varix of fetal umbilical are rare entities characterized by focal aneurysmal dilatation. They account for approximately 4% of umbilical cord anomalies and are thought to be a developmental anomaly rather than a congenital malformation. Their clinical significance has not yet been clearly established. Prenatal diagnosis is made by conventional ultrasound in which the lesion appears as a round or fusiform cystic structure within the fetal abdomen. In addition, it is useful to establish the diameter and the presence of other associated fetal anomalies. Doppler evaluation allows identification of the type of intralesional flow. The perinatal prognosis is favorable when it is identified as an isolated finding. However, in those cases associated with other anatomical/structural alterations, the fetal and neonatal outcome is variable. A case of prenatal diagnosis of intra-abdominal vein varix of fetal umbilical vein is presented.